The curse and blessing of training the unemployed in a changing economy: the case of East Germany after unification - Michael Lechner; Ruth Miquel; Conny Wunsch (Institute for the Study of Labor (IZA), 2005)
We analyse the effects of government-sponsored training for the unemployed conducted during East German transition. For the microeconometric analysis, we use a new, large and informative administrative database that allows us to use matching methods to reduce potential selection bias, to study different types of programmes, and to observe interesting labour market outcomes over 8 years. We find that, generally, all training programmes under investigation increase long-term employment prospects and earnings. However, as an important exception, the longer training programmes are on average not helpful for their male participants. At least part of the explanation for this negative result is that caseworkers severely misjudged the structure of the future demand for skills.
Keywords: J68; 330; active labour market policy; nonparametric identification; matching estimation; causal effects; programme evaluation; panel data; gender differences; Arbeitsmarktpolitik; Weiterbildung; Geschlecht; Arbeitslosigkeit; Panel; Neue Bundesländer